On Certain Properties of the $β$-Flexible Q-Fuzzy Groups and $β$-Flexible Normal Q-Fuzzy Subgroups - Geethalakshmi Manickam (International Journal of Mathematics And its Applications, 2022)
The main purpose of this study is to introduce the new concept of fuzzy set and $β$-flexible fuzzy set. Based on this, the concept of $β$-flexible Q-fuzzy group and $β$-flexible normal Q-fuzzy subgroups are given. The necessary properties related to these two concepts are discussed and proved by using these definitions. We shall also extend some new results related to this subject.